2019
DOI: 10.3389/fmicb.2018.03276
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating the Metabolic Burden of the Co-expression of Secreted Fungal Cellulases in a High Lipid-Accumulating Yarrowia lipolytica Strain by Medium C/N Ratio and a Chemical Chaperone

Abstract: Yarrowia lipolytica, known to accumulate lipids intracellularly, lacks the cellulolytic enzymes needed to break down solid biomass directly. This study aimed to evaluate the potential metabolic burden of expressing core cellulolytic enzymes in an engineered high lipid-accumulating strain of Y. lipolytica. Three fungal cellulases, Talaromyces emersonii-Trichoderma reesei chimeric cellobiohydrolase I (chimeric-CBH I), T. reesei cellobiohydrolase II (CBH II), and T. reesei endoglucanase II (EG II) were expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 119 publications
(165 reference statements)
6
23
0
Order By: Relevance
“…Metabolic burden is a longstanding problem in the engineering of microbes which often leads to undesirable physiological changes (Ding et al, 2018; Wei et al, 2018). In the case of lignocellulosic yeast strains development, physiological responses to metabolic burden are usually evaluated as metabolic performances of the engineered strains such as growth rate, biomass yield and specific substrate consumption rate (Van Rensburg et al, 2012; Ding et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic burden is a longstanding problem in the engineering of microbes which often leads to undesirable physiological changes (Ding et al, 2018; Wei et al, 2018). In the case of lignocellulosic yeast strains development, physiological responses to metabolic burden are usually evaluated as metabolic performances of the engineered strains such as growth rate, biomass yield and specific substrate consumption rate (Van Rensburg et al, 2012; Ding et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of cellulase genes can induce a stressful condition, known as metabolic burden, that may impair the metabolic performances of the recombinant strain (Van Rensburg et al, 2012; Ding et al, 2018; Wei et al, 2018). The concept of metabolic burden arose from previous investigations in this area and became a keystone in yeast synthetic biology and metabolic engineering (Wu et al, 2016; Zahrl et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As the chimera performed the best toward recalcitrant cellulose (Avicell) and showed significant synergism with EGII and CBHII in degrading cellulosic substrates, it was chosen for the final tests with mixed supernatants and the three-strain co-culture. The chimeric TrTeCBHI was also co-cloned under a strong constitutive promoter with the remaining cellulose-degrading activities, EGII and CBHII from T. reesei, as a single integrative expression cassette (Wei et al 2019). The DNA construction was cloned in a "lipidogenic" strain's background resulting in observable conversion of consumed cellulose to lipids.…”
Section: Cellulosementioning
confidence: 99%
“…Noteworthy, the authors observed that high-level overexpression of heterologous secretory proteins caused a drain in the ER (endoplasmic reticulum; site of folding, maturation, and initiation of polypeptide secretion), leading to competition between the cellulase formation and the lipid synthesis, which is also initiated in the ER. It was then pointed that the intrinsic link between cellulase co-expression/secretion and lipid accumulation may hamper generation of high-level lipid production from cellulose by recombinant Y. lipolytica (Wei et al 2019).…”
Section: Cellulosementioning
confidence: 99%
“…These nutraceuticals and lipids compete for the same precursors (acetyl-CoA or malonyl-CoA) with inversed pathway yield in oleaginous yeast, which is a common problem when Y. lipolytica is used as chassis to produce acetyl-CoA-derived chemicals ( Beopoulos et al, 2011 ). A large portfolio of engineering work has been dedicated to mitigate lipogenesis or redirect lipid synthesis for heterologous chemical production ( Ledesma-Amaro and Nicaud, 2016 ; Markham et al, 2018 ), but the heavily engineered strains, even the chromosomally-integrated cell lines, are often difficult to maintain high performance during long-term cultivations ( Roth et al, 2009 ; Xu et al, 2017 ; Wei et al, 2019 ). To solve this challenge, we took advantage of the transcriptional activity of metabolite-responsive promoters ( Skjoedt et al, 2016 ; D'Ambrosio and Jensen, 2017 ; Wan et al, 2019 ), aiming to develop an end-product addiction circuit to rewire cell metabolism in Y. lipolytica .…”
Section: Introductionmentioning
confidence: 99%